Sacitra o br̥hat Liṅga purāṇa - Pradhāna, Kshetramohana, 1916- (Dharmagrantha Shṭora, 1975)
Verse adaptation of the Liṅgapurāṇa, Hindu mythological text, praising the worship of liṅga, symbol of Śiva.